2016
DOI: 10.1103/physreva.94.053614
|View full text |Cite
|
Sign up to set email alerts
|

High-momentum tails as magnetic-structure probes for strongly correlatedSU(κ)fermionic mixtures in one-dimensional traps

Abstract: A universal k −4 decay of the large-momentum tails of the momentum distribution, fixed by Tan's contact coefficients, constitutes a direct signature of strong correlations in a short-range interacting quantum gas. Here we consider a repulsive multicomponent Fermi gas under harmonic confinement, as in the experiment of Pagano et al. [Nat. Phys. 10, 198 (2014)], realizing a gas with tunable SU (κ) symmetry. We exploit an exact solution at infinite repulsion to show a direct correspondence between the value of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 64 publications
(161 reference statements)
10
86
0
Order By: Relevance
“…This expression agrees with the zero order one obtained in [17] and with the one derived for a κ-component balanced spinful Fermi gas in [26] to order 2: in fact one may find the bosonic result by taking the limit of very large number of fermionic components κ → ∞ [36]. The weak-coupling expansion obtained from Section 3.3 reads:…”
Section: Results For Tan's Contactsupporting
confidence: 77%
See 3 more Smart Citations
“…This expression agrees with the zero order one obtained in [17] and with the one derived for a κ-component balanced spinful Fermi gas in [26] to order 2: in fact one may find the bosonic result by taking the limit of very large number of fermionic components κ → ∞ [36]. The weak-coupling expansion obtained from Section 3.3 reads:…”
Section: Results For Tan's Contactsupporting
confidence: 77%
“…Tan's contact of an interacting one-dimensional Bose gas under harmonic confinement has been first studied in reference [17], where a numerical solution based on the local-density approximation (LDA) of the homogeneous-system result has been provided. Analytically, again in the local-density approximation, a strong-coupling expansion has been derived to zeroth order [17], as well as corrections to first and second order [26]. A comparison with matrix-product state simulations has shown that the local-density approximation works surprisingly well [26], even for a small number of particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing more terms of the Taylor expansion of g 1 and n(p) also allows to probe in a finer way the validity of the Renormalization Group-Luttinger liquid approach by comparing their predictions at large distances or short momenta [10]. In the perspective of taking an harmonic trapping into account, it also allows to discuss the validity of the Local Density Approximation [18] by comparison with exact numerics [31]. To this aim, the equation of state from the 1/γ expansion is accurate in the strongly-interacting regime, while the conjecture thereby deduced is also accurate at intermediate γ [32].…”
Section: Discussionmentioning
confidence: 99%